2021
DOI: 10.1002/anie.202107712
|View full text |Cite
|
Sign up to set email alerts
|

A Glucose‐Powered Activatable Nanozyme Breaking pH and H2O2 Limitations for Treating Diabetic Infections

Abstract: The peroxidase‐like activity of nanozymes is promising for chemodynamic therapy by catalyzing H2O2 into .OH. However, for most nanozymes, this activity is optimal just in acidic solutions, while the pH of most physiological systems is beyond 7.0 (even >8.0 in chronic wounds) with inadequate H2O2. We herein communicate an activatable nanozyme with targeting capability to simultaneously break the local pH and H2O2 limitations under physiological conditions. As a proof of concept, aptamer‐functionalized nanozymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 41 publications
0
119
0
Order By: Relevance
“…Besides, the Arrhenius equation demonstrates the chemical reaction rate significantly dependent on temperature [88]. Thus, starting from these basic principles, proper external stimuli such as ATP [40,89], glucose [90], visible light irradiation [39], and NIR light irradiation [91], AMF [92] can enhance the catalytic reaction process of nanozymes through H + , H 2 O 2 , H 2 O 2 affinity, thermal, and active ion concentration modulations, thereby resulting in significantly enhanced bactericidal efficiency of nanozymes under low H 2 O 2 concentration and even neutral pH.…”
Section: External Stimuli Enhancing Catalytic Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the Arrhenius equation demonstrates the chemical reaction rate significantly dependent on temperature [88]. Thus, starting from these basic principles, proper external stimuli such as ATP [40,89], glucose [90], visible light irradiation [39], and NIR light irradiation [91], AMF [92] can enhance the catalytic reaction process of nanozymes through H + , H 2 O 2 , H 2 O 2 affinity, thermal, and active ion concentration modulations, thereby resulting in significantly enhanced bactericidal efficiency of nanozymes under low H 2 O 2 concentration and even neutral pH.…”
Section: External Stimuli Enhancing Catalytic Processesmentioning
confidence: 99%
“…With the aid of ATP, owing to its ability of participation in single electron transfer reaction through complexation with Fe 3 O 4 NPs [96,97], the •OH generation catalyzed by Fe 3 O 4 NPs could be significantly accelerated, resulting in enhanced bactericidal efficiency in presence of H 2 O 2 at neutral pH [38] (figure 3(A)). To break the limitations of local pH and H 2 O 2 under physiological conditions, instead of ATP, Chen et al have constructed a versatile glucose-stimulated nanozymes composed of aptamer-functionalized platinum nanozymes (Apt-PtNZ), glucose oxidase (GOX) and hyaluronic acid (HA) (denoted as APGH) for treating diabetic infections (pH = 7.0-8.0) [90]. With aptamer recognition, APGH could first adhere to bacterial surface, then glucose oxidase would catalyze the glucose oxidation to generate H 2 O 2 and lower the local pH, and finally the POD-mimicking Pt NPs in-situ converted the H 2 O 2 into •OH on bacteria surfaces, subsequently enhancing the antibacterial effect in vitro and in diabetic wounds [90] (figure 3(B)).…”
Section: Atp/glucose Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet these requirements, multivalent aptamer probes, by integrating multiple aptamer units into one nanomaterial or DNA nanostructure, have been employed to enhance the binding affinity via the multivalent effect. It has been shown the multivalent aptamer probes strategy increased local ligand density or synergistic interaction 13 - 15 . In particular, benefiting from the great progress of DNA nanotechnology, series of DNA nanostructures including DNA tetrahedron 10 , 16 , 17 , DNA nanowire 18 , DNA nanohydrogel 19 , 20 , RCA-based DNA nanostructure 21 , 22 , etc., have been exploited and used as scaffolds to incorporate multivalent aptamers.…”
Section: Introductionmentioning
confidence: 99%
“…Many nanomaterials, such as cobaltosic oxide nanoparticles ( Wang P. et al, 2019 ), manganese dioxide ( Zou et al, 2021 ), graphene oxide hybrid ( Wang Q. et al, 2021 ; Zhang et al, 2021e ), nanoceria ( Zhang J. et al, 2021 ), carbon dots ( Li et al, 2022 ), VS 2 ( Huang et al, 2018 ), PtS 2 ( Zhang W. et al, 2021 ), MoS 2 ( Zhang X. et al, 2021 ; Tan et al, 2021 ), and WS 2 ( Nandu et al, 2021 ), had been shown to possess a similar peroxidase-like activity. These nanozymes had been used in various fields including biosensing ( Wang L. et al, 2021 ; Liu et al, 2021 ), bioimaging ( Gao et al, 2017 ; Liu et al, 2019 ), therapeutics ( Chen et al, 2021 ; Zhang et al, 2021d ; Zhang et al, 2021e ; Hai et al, 2021 ), and biofuel cells ( Le and Il, 2021 ) as substitutes for natural enzymes. Among these nanozymes, Co 3 O 4 nanomaterials exhibit multienzyme activities at different pH conditions ( Wang P. et al, 2019 ) which had been used to construct enzyme-free glucose sensors and other biosensing applications.…”
Section: Introductionmentioning
confidence: 99%